Performance Assessment of Public Health Center Madising Na Mario Parepare, South Sulawesi, Indonesia - Ajeng Dyah Pythaloka; Muhammad Yusri Abadi; Darmawansyah Darmawansyah (International Journal of Applied Biology, 2019)
Implement health efforts both public health efforts are first rate and first rate individual health efforts are needed health center management be integrated and continuous in order to produce the performance of Public Health Center effective and efficient. This study aims to find out about the picture of the level of achievement of performance results pertaining to quality health center health center services, management of health centers and health care Public Health Center Madising Na Mario Pare-pare. This research method is quantitative descriptive method, whereby it purports to describe the level of achievement of the performance results of health centers. From the research achievement of quality performance owned health center services obtained an average value of 9,7 performance with good performance categories. Public Health Center management obtained an average performance score of 10 with a good performance categories. Health services obtained the value of the average performance of 70,9% with less performance categories. Therefore, efforts to improve the performance of health centers needed professional human resources and improvement of health facilities, especially the budget required.